2014
DOI: 10.4049/jimmunol.1401258
|View full text |Cite
|
Sign up to set email alerts
|

Axl Receptor Blockade Protects from Invasive Pulmonary Aspergillosis in Mice

Abstract: Aspergillus fumigatus is a sporulating fungus found ubiquitously in the environment, which is quickly contained in the immunocompetent host but can cause lethal invasive aspergillosis in the immunocompromised host. We have recently demonstrated that Axl (one member of the Tyro3, Axl, Mertk receptor family) is a key regulator of antiviral immune responses in the lung. In this study, we investigated the role of Axl in antifungal immunity in a model of invasive pulmonary aspergillosis (IPA). In this model, Asperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…It is important that Gas6/Axl signaling dramatically enhances allergic immune responses during FI‐RSV VED, even though it simultaneously attenuates RSV‐F protein‐induced activation of DCs with the concomitant suppression of MHC II, CD40 and CD80 expression. Furthermore, Gas6/Axl also strongly suppresses IFN‐γ production in innate immune models 28 , 47 . These results seem to support the second hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…It is important that Gas6/Axl signaling dramatically enhances allergic immune responses during FI‐RSV VED, even though it simultaneously attenuates RSV‐F protein‐induced activation of DCs with the concomitant suppression of MHC II, CD40 and CD80 expression. Furthermore, Gas6/Axl also strongly suppresses IFN‐γ production in innate immune models 28 , 47 . These results seem to support the second hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…H5N1 infection resulted in significant upregulation of a number of inflammatory cytokines/chemokines genes, including AXL and STING, which were significantly reduced by apocynin treatment to a level lower than that observed in uninfected cells (Table S4 ). It has been previously demonstrated that anti-AXL antibody treatment of PR8-infected mice significantly reduced lung inflammation and virus titers 40 . STING has been shown to be important for promoting anti-viral responses, as STING-knockout THP-1 cells produce less type I IFN following influenza A virus infection 41 .…”
Section: Discussionmentioning
confidence: 96%
“…Other possible mechanisms involved in the enhanced susceptibility to secondary bacterial infections include the attenuation of antibacterial protective immunity. In a previous study, we demonstrated that RSV stimulates the growth arrest-specific 6 (Gas6)/Axl axis, which regulates the anti-RSV and antifungal Th1 immune responses (16,17). Mechanistically, Axl, a high-affinity Gas6 receptor, was reported to attenuate the ability of dendritic cells (DCs) to respond to pathogen-associated molecular patterns through the DC-intrinsic Toll-like receptor (TLR) (18,19).…”
Section: Introductionmentioning
confidence: 99%